REVERSIBLE INACTIVATION OF TYPHUS RICKETTSIAE : I. INACTIVATION BY FREEZING - Bovarnick, Marianna R. (The Rockefeller University Press, 1954)
Rickettsiae that have been frozen and thawed in isotonic salt solutions show greatly decreased toxicity for mice, hemolytic activity, respiration, and infectivity for eggs. All these properties can be partially restored by incubation of the rickettsiae in the presence of DPN and coenzyme A for 2 hours at 34°C. The extent of both inactivation and of subsequent reactivation is markedly affected by the presence of low concentrations of sucrose during the process of freezing and thawing. It has been shown that DPN is present in rickettsial suspensions and that in preparations that have not been frozen, the DPN sediments with the rickettsiae. After freezing in isotonic salt solution the DPN becomes non-sedimentable.